Russian Federation - from strength to weakness, from West to East, from a permanent member to a potential outsider - Lupu, Mădălina Elena (Technium Social Sciences Journal, 2023)
This article focuses on the Russian Federation as a state in between strength and weakness, West and East, a permanent member and a potential outsider. It begins with the Russian decline in power, using as measurable indicators the five dimensions of security promoted by the Copenhagen School of security studies. It continues with Russian foreign policy reconfigured from West to East and with proposals regarding the United Nations reform and the establishment of a new Special Court to sanction the Russian political and military leader’s crime aggression against Ukraine. In the end, the scenario method is a research method. We advance three possible scenarios: the most likely scenario for the Russian state that is based on the Russian state defeat, war reparations imposed and accountability for political and military leaders; the worst-case scenario that involves the tactical nuclear weapons use in Ukraine and an international answer accordingly and the optimistic scenario for the Russian state that involves winning the war, but without international recognition and legitimacy for victory.